PENGAMATAN GEJALA GULMA YANG DISEBABKAN OLEH JAMUR DI BUKIT KOR, TERENGGANU - Lubis, Riszky Ardyansyah; Yusuf, Mukhtar; Sidique, Siti Nordahliawate Mohammed (Fakultas Pertanian, Universitas Janabadra, 2024)
Observation of weed symptoms caused by fungi in Bukit Kor, Marang, Terengganu, Malaysia which was conducted in September 2023 in the agricultural land of Bukit Kor, Marang, Terengganu. The research was conducted using descriptive methods by making direct observations to the field taking direct weed samples and identifying fungi that cause disease in weeds. Sampling was done using quadrats, 1x1 quadrat size. The results showed that there were 5 types of weeds that had disease symptoms, namely Alang-alang (Imperata cylindrica), Leunca (Solanum americanum), Buffalo grass (Paspalum conjugatum), Goletrak (Boreria alata) and Jelumpang grass (Melochia chortoriafolia). The fungi found in the study were Bipolaris sp, Exserohilum sp, Culvularia sp, Cylidrocarpon sp and Culvularia sp. Of the five fungi, the dominant disease carrier was Culvularia sp. Keywords: weeds, Bukit Lor, symptoms. INTISARIPengamatan gejala gulma yang disebabkan oleh jamur di Bukit Kor, Marang, Terengganu, Malaysia yang dilakukan pada bulan September 2023 di lahan pertanian Bukit Kor, Marang, Terengganu. Penelitian dilakukan menggunakan metode deskriptif dengan melakukan pengamatan langsung ke lapangan mengambil langsung sampel gulma dan mengidentifikasi jamur penyebab penyakit pada gulma. Pengambilan sampel dilakukan dengan menggunakan kuadrat, ukuran kuadrat 1x1. Hasil penelitian menunjukkan ada 5 jenis gulma yang memperlihatkan gejala penyakit, yaitu Alang-alang (Imperata cylindrica), Leunca (Solanum americanum), Rumput kerbau (Paspalum conjugatum), Goletrak (Boreria alata) dan Rumput jelumpang (Melochia chortoriafolia . Jamur yang ditemukan pada penelitian adalah Bipolaris sp, Exserohilum sp, Culvularia sp, Cylidrocarpon sp dan Culvularia sp. Dari kelima jamur tersebut yang dominan sebagai pembawa penyakit adalah Culvularia sp. Kata kunci: gulma, Bukit Lor, gejala